INSTITUTIONAL AND INVESTMENT FACTORS IN THE DEVELOPMENT OF HOUSING CONSTRUCTION IN UZBEKISTAN (Global Conference on Multidisciplinary Research and Innovation, 2026)
The housing construction sector plays a crucial role in the socio-economic development of Uzbekistan, influencing urbanization processes, investment activity, and living standards of the population. In recent years, the government has implemented a series of institutional reforms and investment initiatives aimed at expanding housing supply and improving affordability. This thesis examines the relationship between investment mechanisms and institutional factors in the development of housing construction in Uzbekistan. The study is based on the analysis of policy reforms, statistical data, and international experience. The results indicate that sustainable development of the housing sector depends on the effective coordination of state regulation, financial instruments, and private sector participation.
Keywords: housing construction, Uzbekistan, investment policy, institutional reforms, urban development, public-private partnership